Maternal and perinatal morbidity and mortality in COVID-19 positive obstetric patients with medical disorders in tertiary care hospital in North India - Goyal, Gunjan; Tongaria, Khushboo; Kumar, Sachin; Thakran, Brijesh Kumar; Yadav, Mohini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Coronavirus disease (COVID-19) is an infectious disease caused by a newly discovered coronavirus. Most people infected with the COVID-19 virus experienced mild to moderate respiratory illness. Coronavirus is known to human kind since 1930. It was first discovered in domesticated chicken with symptoms of pulmonary infection. The aim and objective was to study clinical profile of patients presented with medical disorders in COVID-19 positive pregnant women. Methods: Present retrospective COHORT study included 50 COVID-19 positive obstetrics patients. The study was conducted in the department of obstetrics and gynaecology, World college of medical sciences and research, Jhajjar (Haryana). Retrospective review of medical records of all pregnant patients with pre-existing medical disorders or those suspected with medical disorders on the basis of clinical and/or laboratory data from 1 April 2020 through 30 September 2020. Results: Mean age of the women was 27.46±4.16 years with age range of 20-35 years. Mean period of gestation was 33.26±8.35 weeks. A total of 33 (66%) women were found to be COVID-19 positive due to close contact. 29 (58%) women were found to be asymptomatic and 17 (34%) had various other COVID-19 symptoms. In 17 (34%), sore throat was the commonest symptoms followed by cough, myalgia and fatigue, that is, 13 (26%) each. Fever at the time of admission was present in 9 (18%) women and postpartum fever was observed in 4 (8%) women. Mean hospital stay was 9.24±3.25 days. A total of 29 (58%) women underwent caesarean delivery and 21 (42%) had normal vaginal delivery. Mean postoperative hospital stay was 4.48±2.24 days. In 9 women, postoperative complications were seen. A total of 8 babies admitted to NICU due to various complications. Two babies expired during the study period. Conclusions: In the present retrospective COHORT study, the majority of the pregnant women with COVID-19 infection had mild symptoms with no severe illness. Mother-to-child transmission of COVID-19 cannot be ruled out. The impacts of COVID-19 infection on patients with medical disorders during pregnancy were seen.